Potencial antiproliferativo e determinação de compostos fenólicos de Cordia trichotoma (Vell.) Arráb. ex Steud. - Pavanelo, Leonardo Bachio (2014)
Cordia trichotoma (Vell.) Arráb. ex Steud., known as louro-pardo, belongs to the Boraginaceae family and is widely distributed in Brazil. In Rio Grande do Sul (RS), is found in the Alto Uruguai and Depressão Central. This is a large species, reaching 35 meters in height. It is appreciated for the quality of its wood, which has scenic value, and can be employed in the recovery of degraded areas; its leaves have medicinal value, which are used to prepare teas. These, in turn, are used to treat kidney diseases, rheumatism, arthritis and rickets. The Allium cepa test is used as a bioindicator of genotoxic and antiproliferative capacity of aqueous extracts (teas) prepared with different plant materials such as leaves, flowers, fruit and bark. This study aimed to evaluate the antiproliferative potential of infusions of four populations of C. trichotoma on the cell cycle of A. cepa, as well as to analyze the phenolic compounds in infusions. The leaves and fruits of louro-pardo, used in the assembly of the experiments, were collected in three municipalities in the RS. For experiment 1, teas (infusions ) leaves were used , and for the experiment 2, the fruits were used. Six groups of four onion bulbs rooting in water were used, which consisted of six treatments and four replications for each of the populations of C. trichotoma in both experiments. The treatments were: T1 - negative control in distilled water ; T2- infusion of 5 g.L-1 ; T3- infusion of 20 g.L-1 ; T4- infusion of 5 g.L-1 ; T5- infusion of 20 g.L-1 ; T6- positive control in glyphosate 2% . After treatments, the roots of A. cepa were fixed, conserved and then slides prepared by squashing technique, stained with 2% acetic orcein. Therefore, it were subsequently analyzed under a microscope 40x. It were counted 500 cells by bulb, totaling 2000 cells for each treatment and for each of the populations. The mitotic index was calculated as well as the verification of possible irregularities in the cell cycle. Phenolic compounds were determined by the technique of high performance liquid chromatography (HPLC). The results showed a statistically significant difference for the increased inhibition of cell division as the concentration of infusions of louro-pardo in both experiments, no genotoxicity was observed in extracts. Compounds that appeared in larger quantities were caffeic acid, rosmarinic acid and ellagic acid. C. trichotoma infusions prepared in different concentrations exhibit antiproliferative potential and have no genotoxic activity on the cell cycle of A. cepa. The results obtained in the area of genotoxicity as well as the phenolic found in C. trichotoma infusions constitute new information for this species.